Nfix Promotes Survival of Immature Hematopoietic Cells via Regulation of c‐Mpl. (27th February 2018) - Hall, Trent; Walker, Megan; Ganuza, Miguel; Holmfeldt, Per; Bordas, Marie; Kang, Guolian; Bi, Wenjian; Palmer, Lance E.; Finkelstein, David; McKinney‐Freeman, Shannon
Abstract: Hematopoietic stem and progenitor cells (HSPCs) are necessary for life‐long blood production and replenishment of the hematopoietic system during stress. We recently reported that nuclear factor I/X ( Nfix) promotes HSPC survival post‐transplant. Here, we report that ectopic expression of Nfix in primary mouse HSPCs extends their ex vivo culture from about 20 to 40 days. HSPCs overexpressing Nfix display hypersensitivity to supportive cytokines and reduced apoptosis when subjected to cytokine deprivation relative to controls. Ectopic Nfix resulted in elevated levels of c‐Mpl transcripts and cell surface protein on primary murine HSPCs as well as increased phosphorylation of STAT5, which is known to be activated down‐stream of c‐MPL. Blocking c‐MPL signaling by removal of thrombopoietin or addition of a c‐MPL neutralizing antibody negated the antiapoptotic effect of Nfix overexpression on cultured HSPCs. Furthermore, NFIX was capable of binding to and transcriptionally activating a proximal c‐Mpl promoter fragment. In sum, these data suggest that NFIX‐mediated upregulation of c‐Mpl transcription can protect primitive hematopoietic cells from stress ex vivo. Stem Cells 2018;36:943–950 Abstract : Hematopoietic stem and progenitor cells (HSPCs) are necessary for life‐long blood production and replenishment of the hematopoietic system during stress. Here, we show that nuclear factor I/X ( Nfix ) is capable of protecting HSPC from stress‐induced apoptosis during ex vivo culture. This protection relies on proper thrombopoietin/c‐MPL signaling, as NFIX directly regulates c‐Mpl expression.